2018
DOI: 10.12659/msm.910953
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Stathmin 1 Expression in Osteosarcoma Shows an Association with Metastases and Poor Patient Prognosis

Abstract: BackgroundOsteosarcoma is the most common primary bone cancer and has a broad spectrum of histological subtypes. Stathmin 1 (STMN1) is a cytosolic phosphoprotein that is expressed in several types of cancer. The aim of this study was to evaluate the expression levels of STMN1 in osteosarcoma with clinicopathological characteristics and patient prognosis.Material/MethodsThe expression of STMN1 in tumor tissue from 94 patients with OS was detected and evaluated using an immunohistochemical score to divide the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…It would be meaningful to investigate the real correlation between them in future research. Several previous studies showed stathmin could directly predict the prognosis of cancer patients, but we did not obtain accordant results in this study. The possible reason is that patients in this study, following the inclusion criteria for our clinical trial, were all at clinical stages III and IVA.…”
Section: Discussioncontrasting
confidence: 97%
“…It would be meaningful to investigate the real correlation between them in future research. Several previous studies showed stathmin could directly predict the prognosis of cancer patients, but we did not obtain accordant results in this study. The possible reason is that patients in this study, following the inclusion criteria for our clinical trial, were all at clinical stages III and IVA.…”
Section: Discussioncontrasting
confidence: 97%
“…Osteosarcoma is a primary malignant tumor common in adolescents or children under the age of 20. This disease has the following clinical features: strong invasiveness, poor prognosis, and high metastatic rate [13][14][15][16][17]. Although osteosarcoma is treated in a variety of ways, local tumor recurrence, metastasis, and multi-drug resistance after surgery and low rate of tumor necrosis at the time of the surgery seriously hamper the postoperative condition and prognosis of osteosarcoma patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although these ve predictors were easy to obtain, it was undeniable that these predictors were all non-speci c OSC predictors and may lack certain speci city. Some biomarkers may be incorporated into these prognostic models to improve speci city, such as immunohistochemical markers [41], radiomics [42,43], and recently newly applied non-coding RNAs [44,45]. 5.…”
Section: Discussionmentioning
confidence: 99%